2020
DOI: 10.24843/ljlc.2020.v09.i01.p05
|View full text |Cite
|
Sign up to set email alerts
|

The Types of Women Language Features Found in the Fault in Our Stars Movie

Abstract: This study entitled The Types of Women Language Features found in The Fault in Our Stars movie. The study aimed to find out the types of women language features used by the female main character. This study focused on Lakoff’s theory (1975) about women language features. This study applied qualitative and quantitative methods in revealing the data. The study used note taking as a technique to get a valid data in collecting the data. The findings showed that there were 9 out of 10 types of women language featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…It indicated that both tag questions are used to emphasize the point of the question asked. This is in line with study conducted by Setyani & Laila (2019) who stated that women use tag question for as a confirmation to the previous statement or question uttered by the speaker. 3.…”
Section: Feelingssupporting
confidence: 91%
“…It indicated that both tag questions are used to emphasize the point of the question asked. This is in line with study conducted by Setyani & Laila (2019) who stated that women use tag question for as a confirmation to the previous statement or question uttered by the speaker. 3.…”
Section: Feelingssupporting
confidence: 91%